Colophonic Reflections on Dǝrsanä Ṣǝyon and Kǝbrä Nägäśt - Tefera, Amsalu (Aethiopica, 2014)
This article briefly describes and discusses three Ethiopic manuscripts jointly containing Dǝrsanä Ṣǝyon ‘homily on [the glory of] Zion’ followed by Kǝbrä Nägäśt ‘Dignity of Kings’ as a single literary unit. It also lists the incipit and desinit of each manuscript with their peculiar features. Finally, an edition and translation of their lengthy colophon is presented.